The Multi-Functional Calcium/Calmodulin Stimulated Protein Kinase (CaMK) Family: Emerging Targets for Anti-Cancer Therapeutic Intervention - Joshua S. Brzozowski; Kathryn A. Skelding (MDPI AG, 2019)
The importance of Ca2+ signalling in key events of cancer cell function and tumour progression, such as proliferation, migration, invasion and survival, has recently begun to be appreciated. Many cellular Ca2+-stimulated signalling cascades utilise the intermediate, calmodulin (CaM). The Ca2+/CaM complex binds and activates a variety of enzymes, including members of the multifunctional Ca2+/calmodulin-stimulated protein kinase (CaMK) family. These enzymes control a broad range of cancer-related functions in a multitude of tumour types. Herein, we explore the cancer-related functions of these kinases and discuss their potential as targets for therapeutic intervention.